THE INTERACTION BETWEEN TEACHING COMPETENCIES AND SELF-EFFICACY IN FOSTERING ENGAGEMENT AMONGST DISTANCE LEARNERS: A PATH ANALYSIS APPROACH (Malaysian Journal of Learning and Instruction, 2022)
Purpose - Distance learners are expected to actively participate in online learning settings to improve their cognitive level and promote more meaningful learning. However, without specific teaching skills and competencies from the instructors together with belief and capability of the distance learners themselves, their engagement in online learning would not be achieved. Limited studies have examined the extent of self-efficacy in encouraging student engagement in learning, especially within online learning settings. Thus, this study examined self-efficacy as a moderator to test its influence on the relationship between online teaching competencies and student engagement.Methodology - This quantitative research was conducted using the purposive sampling technique. This study involved 321 distance learners from a Malaysian public university. The questionnaire was created using SurveyMonkey, and the measurement items were adopted from past research with acceptable reliability. This study utilised partial least squares (PLS) 3.0 to test the hypothesis via correlation and path analysis.Findings - Contrary to expectations, the findings contributed to the literature that online teaching competencies and self-efficacy were not significantly related to student engagement. The association between online teaching competencies and student engagement was shown to be moderated by self-efficacy. This finding is aligned with Bandura’s (2001) social cognitive theory which states that personal factors such as self-regulation, self-efficacy, and interest are impacted in the distance education context.Significance - The results of this study can benefit online course instructors in Malaysian distance educational institutions to develop courses that enhance online learners’ self-efficacy. Online teaching competencies employed by online distance learners can be the primary objective when developing faculty development programmes that aim to coach online instructors to be competent in online teaching. Moreover, institutions are encouraged to introduce other online learning platforms to facilitate training of its practitioners in order to accelerate successful online teaching and learning experiences.